2014
DOI: 10.1037/a0036150
|View full text |Cite
|
Sign up to set email alerts
|

Testing the concept of relational entitlement in the dyadic context: Further validation and associations with relationship satisfaction.

Abstract: The sense of relational entitlement is the perception one has of what one deserves from one's partner, and it may play a crucial role in determining the quality of a couple's relationship. However, the concept was only recently subjected to empirical examination. The main goals of the current study were to continue the work initiated by the scale developers (Tolmacz & Mikulincer, 2011) by (1) further validating the Sense of Relational Entitlement Scale (SRE) in a sample of adult couples; and (2) examining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
5
14
0
1
Order By: Relevance
“…It seems intuitive that CSA survivors should be reluctant to express their needs and wishes in romantic relationships and to doubt their basic legitimacy, as reflected by their high levels of restricted SRE. Previous studies have shown a restricted sense of entitlement to be associated with high levels of distress and loneliness, negative mood, neuroticism, depression, and social anxiety, and with low levels of relationship satisfaction, life satisfaction (George-Levi, Vilchinsky, Tolmacz, & Liberman, 2014; Tolmacz & Mikulincer, 2011), self-efficacy, and low self-esteem (Tolmacz, Efrati, & Ben-David, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It seems intuitive that CSA survivors should be reluctant to express their needs and wishes in romantic relationships and to doubt their basic legitimacy, as reflected by their high levels of restricted SRE. Previous studies have shown a restricted sense of entitlement to be associated with high levels of distress and loneliness, negative mood, neuroticism, depression, and social anxiety, and with low levels of relationship satisfaction, life satisfaction (George-Levi, Vilchinsky, Tolmacz, & Liberman, 2014; Tolmacz & Mikulincer, 2011), self-efficacy, and low self-esteem (Tolmacz, Efrati, & Ben-David, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In further validation of the SRE by George-Levi et al (2014) , the intercorrelations between “assertive entitlement” and “entitlement expectations” (one of the factors that in the original study (2011) seemed to tap different aspects of inflated forms of entitlement) were found to be significant and positive. The authors suggested that these two factors representing a more secure, mature, healthy, or assertive sense of entitlement and suggested that the entitlement expectations items should not be included in the inflated factor.…”
Section: Introductionmentioning
confidence: 84%
“…We administered the SRE-R to a large community sample of adults in significant romantic relationships and aimed to validate its two-factor structure (inflated entitlement, restricted entitlement). We also aimed to replicate associations found in previous studies (that used the 33-item SRE scale) between sense of relational entitlement and other relational variables, such as attachment orientations and pathological concern (e.g., Tolmacz and Mikulincer, 2011 ; George-Levi et al, 2014 ; Shavit and Tolmacz, 2014 ). In addition, we aimed to examine associations between the two SRE-R factors, relational obsessions/compulsions and authenticity in romantic relationships.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Embora a maioria dos estudos evidencie que a adesão a mitos conjugais pode comprometer a qualidade do relacionamento (Caldwell & Woolley, 2008;Ercegovac & Bubić, 2016;Fowler, 2000), um estudo americano feito com mulheres indica que ela pode predizer experiências conjugais positivas (Casad, Salazar, & Macina, 2015 (Neff & Geers, 2013). Na mesma direção, pesquisa realizada com 120 casais heterossexuais israelenses em casamentos de longa duração demonstrou que ter expectativas apropriadas a respeito dos deveres do parceiro(a) para consigo se relaciona com bons níveis de satisfação conjugal, já que as expectativas também têm como papel indicar o tipo de investimento feito no relacionamento (George-Levi, Vilchinsky, Tolmacz, & Liberman, 2014).…”
Section: Introductionunclassified